Customer-Centric Strategies: Navigating the Dynamics of Marketing Management for Competitive Advantage - Akbar, Mohammad Aldrin (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
The purpose of this study is to examine the significance of customer-centric strategies in marketing management and their implications for organizational success. Adopting a literature review approach, this research synthesizes insights from various disciplines to elucidate the multifaceted nature of customer-centricity. The research design employs a qualitative approach, drawing on existing scholarship to elucidate key concepts and frameworks in customer-centricity. The findings highlight the paramount importance of prioritizing customer needs and preferences, aligning organizational culture and processes with customer goals, and leveraging technological innovations to enhance customer experiences. The discussion underscores the challenges and opportunities presented by the digitalization of commerce, emphasizing the need for organizations to adapt and innovate in response to changing consumer behaviors and market dynamics. The implications of this study extend to both theory and practice, offering valuable insights for academics, practitioners, and policymakers alike. By embracing a customer-centric mindset and integrating interdisciplinary perspectives, organizations can develop robust strategies that drive sustainable competitive advantage in today's dynamic markets.